2014
DOI: 10.1371/journal.pone.0104986
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Antibiotic Resistance Mechanisms in Clinical Burkholderia cepacia Complex Isolates: An Emphasis on Efflux Pump Activity

Abstract: Due to the limited information of the contribution of various antibiotic resistance mechanisms in clinical Burkholderia cepacia complex isolates, Antibiotic resistance mechanisms, including integron analysis, identification of quinolone resistance-determining region mutations, measurement of efflux pump activity, and sequence analysis of efflux pump regulators, were investigated in 66 clinical B. cepacia complex isolates. Species were identified via recA-RFLP and MALDI-TOF. Four genomovars were identified by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 36 publications
3
41
0
1
Order By: Relevance
“…High-level ciprofloxacin resistance (MIC>256 μg/ml) required an additional Ser80Leu mutation in the ParC QRDR (Pope et al, 2008). Similar gyrA mutations were identified in a majority of levofloxacin resistant isolates studied in a survey of resistance mechanisms in Bcc (Tseng et al, 2014). The resistant isolates contained Gly81Asp, Thr83Ile, and Asp87His mutations.…”
Section: Burkholderia Cepacia Complex Organismssupporting
confidence: 59%
See 1 more Smart Citation
“…High-level ciprofloxacin resistance (MIC>256 μg/ml) required an additional Ser80Leu mutation in the ParC QRDR (Pope et al, 2008). Similar gyrA mutations were identified in a majority of levofloxacin resistant isolates studied in a survey of resistance mechanisms in Bcc (Tseng et al, 2014). The resistant isolates contained Gly81Asp, Thr83Ile, and Asp87His mutations.…”
Section: Burkholderia Cepacia Complex Organismssupporting
confidence: 59%
“…Of these RND-3, RND-4, and RND-10 (also known as CeoAB-OpcM) correspond to B. pseudomallei AmrAB-OprA, BpeAB-OprB and BpeEF-OprC, respectively, although the resistance patterns bestowed by the respective pumps are somewhat different, with the exception of RND-10 and BpeEF-OprC whose resistance profiles are very similar (Podnecky et al, 2015). An inventory of B. cenocepacia resistance mechanisms showed that efflux pump activity is prevalent in this bacterium and that mutations in the RND-3 pump regulator are the major cause of efflux pump activity and RND-3 mediated antibiotic resistance (Tseng et al, 2014). In B. vietnamiensis , aminoglycoside resistance emerges during chronic infection or after in vitro exposure to aminoglycosides and is the result of AmrAB-OprM efflux pump expression, which is most likely a homolog of B. pseudomallei and B. thailandensis AmrAB-OprA (Jassem et al, 2014; Jassem et al, 2011).…”
Section: Burkholderia Cepacia Complex Organismsmentioning
confidence: 99%
“…With 16 RND pumps present in B. cenocepacia strain J2315, their differential roles in drug resistance of planktonic and biofilm cells were investigated (613). Another study showed the high prevalence of RND pump-overproducing clinical isolates (particularly RND-3 overproducers) (616). However, the data regarding the effect of PA␤N on antibi-otic susceptibility appeared contradictory.…”
Section: Burkholderia Sppmentioning
confidence: 99%
“…The genome of another CF pathogen, B. cenocepacia, contains genes coding for 22 RND efflux systems (37)(38)(39)(40), and high levels of expression of these efflux pumps are frequently observed in B. cepacia complex clinical isolates (41). Exposure of B. cenocepacia biofilms to the disinfectant chlorhexidine results in the up-regulation of eight RND family efflux pumps (42).…”
Section: Burkholderia Cenocepaciamentioning
confidence: 99%